种利用太阳能低成本生产过氧化氢和氢气的电解方法 (2018)
种利用太阳能低成本生产过氧化氢和氢气的电解方法，采用晶向为{111}、{110}、{100}或{010}的纯相或掺杂钒酸铋单晶片作为电解槽的阳极，将碱性电解液加入电解槽后，在保持电解槽内的电解液处于暗态条件的同时，使阳极处于光照下，在电解槽的阳极和阴极上外加偏压，使阳极生成过氧化氢，阴极生成氢气。与现有技术相比，采用单晶半导体氧化物替代昂贵的金属铂作为电解阳极，大幅降低了生产成本。单晶半导体氧化物阳极比传统电解硫酸或硫酸盐的铂电极所需的起始电压更小，在电能利用效率上比铂电极高。而在光照条件下，外加偏压为0.4 V即可在阳极区检测到HO的生成，所需的电能更少，更为节能。 Provided is an electrolysis method for producing hydrogen peroxide and hydrogen through solar energy at low cost. A pure-phase or pucherite doped single crystal wafer with the crystal orientation of {111} or {110} or {100} or {010} is adopted as an anode of an electrolytic cell; after an alkaline electrolyte is added into the electrolytic cell, the electrolyte in the electrolytic cell is kept in the dark state condition, and meanwhile the anode is in illumination; and bias voltages are additionally applied to the anode and a cathode of the electrolytic cell, the anode generates hydrogen peroxide, and the cathode generates hydrogen. Compared with the prior art, single crystal semiconductor oxide is used for replacing expensive